"تأثير وسائل الإعلام المرئية على مسار الأزمة الخليجية 2017-2018 دراسة مقارنة لقناتي العربية والجزيرة " - محمد السايح, حافظ (جامعة الوادي university el-oued)
"يشهد عالمنا اليوم العديد من الأزمات حيث تعددت الأسباب والنتائج لهذه الأزمات واختلفت طرق التناول الإعلامي لهذه الأزمات ومن خلال هذه الدراسة توصلنا إلى مايلي: - الإعلام سلاح قوي في إدارة الأزمات والتحكم في مسارها باختلاف وسائله - توظيف الإعلام من أجل الوصول إلى قناعات الجمهور والسيطرة على أفكاره وكسب ولائه أهم ما يميز عصرنا اليوم - القنوات الإخبارية في العالم العربي تشهد تنافس كبير خاصة العربية والجزيرة - الأزمة الخليجية أثبتت حدة ا"Abstract: There are many crises in our world today, where the causes and consequences of these crises varied and the methods of media handling of these crises varied. Through this study we reached the following: - Media is a powerful weapon in the management of crises and control the course of various means - Employment of media in order to reach the convictions of the public and control the ideas and gain Confidence is the most important characteristic of our time today - News channels in the Arab world are witnessing great competition, especially the AlArabiya and the Aljazeera - The Gulf crisis has proved the severity of the media conflict and its role in controlling crise
م.س.ع.19
Keywords: الإعلام- الأزمات - الأزمة الحليجية- قناة العربية -قناة الجزيرة; Media - Crisis - Gulf crisis - Al Arabiya - Al Jazeera